Changes in Intestinal Microbiota and Their Relationship With Patient Characteristics in Colorectal Cancer - Lu Zhao; Yongkun Fang; Jingqiu Zhang; Chen Wei; Hao Ji; Jiahao Zhao; Daorong Wang; Dong Tang (Clinical Medicine Insights: Oncology)
Background: Gut microbiota are associated with the pathological features and development of colorectal cancer (CRC); however, how gut microbiota changes in patients with CRC is unknown. This study investigated the role of gut microbiota in the development and progression of CRC by retrospectively comparing the structural differences between the gut microbiota of patients with CRC and healthy individuals. Methods: Together with clinical data, we collected fecal samples from patients with CRC (n = 18) and healthy controls (n = 18) and performed 16S rRNA gene sequencing and alpha and beta diversity analysis to compare microbiota richness and diversity. Based on the differences in microbiota between the CRC and control groups, we identified disease-specific microbial communities after relevant factors. PICRUSt2 software was used to predict the differential microbial functions. Results: The CRC and control groups differed in both composition and abundance of intestinal microbiota. Firmicutes and Bacteroidetes were the most abundant phyla in both groups, while Verrucomicrobi was significantly more abundant in the CRC group. Megamonas , Lachnospira , and Romboutsia were more abundant in the control group; 18 genera differed significantly in abundance between the groups, which were found to involve 21 metabolic pathways. The distribution and abundance of gut microbiota differed significantly between patients with CRC with and without lymph node metastasis; at the genus level, the abundance of Rothia and Streptococcus was significantly higher and that of Bacteroides , Parabacteroides , and Oscillibacter was significantly lower in patients with lymph node metastasis. Conclusions: The gut microbiota is altered in CRC patients compared with healthy individuals, with specific changes in the microbiota associated with clinical and pathological features such as tumor stage, lymph node involvement, and tumor differentiation. Our findings elaborate to some extent on the link between the gut microbiota and CRC.